Participation of children and youth with cerebral palsy in rural Uganda: Activity attendance and involvement compared with peers without cerebral palsy - Andrews, Carin; Kakooza-Mwesige, Angelina; Forssberg, Hans (Karolinska Institutet, 2022)
AIM: To compare participation attendance and involvement of children and youth (C&Y) with and without cerebral palsy (CP) in a low-income area of eastern Uganda.
METHOD: Eighty-two C&Y with CP aged 6–22 years and 81 age- and sex-matched C&Y without CP participated in the study. Data on attendance and involvement in 20 home and community activities were obtained using the instrument "Picture My Participation". Non-parametric statistical methods were used to assess between-group differences. Effect size estimates were calculated.
RESULTS: Pooled attendance across all activities was significantly lower in C&Y with CP than in C&Y without CP (P<0.001) and for each activity item (P=0.004 to P<0.001). Effect sizes for each activity were 0.2–0.7. Between-group differences were larger for community activities than for home activities. Pooled involvement across all activities was less in the CP group (P<0.001) and for each activity (P=0.014 to P<0.001). Effect sizes for each activity were 0.2–0.5. C&Y at GMFCS level I–II had higher attendance (P<0.001) and involvement (P=0.023) than those at GMFCS III–V.
INTERPRETATION: Participation attendance and involvement of young people living with CP in Uganda were restricted, especially for community activities. There is a need to identify context-specific participation barriers and develop strategies to overcome them.
Eighty-two children and youth with cerebral palsy aged 6-22 years and 81 age- and sex-matched children and youth without CP participated. Motor function, self-care skills, and social functions were assessed, and caregivers were interviewed on behalf of their children using Picture My Participation (PMP). PMP measures participation in 20 home and community activities, and was developed for use in low and middle-income countries. The instrument consists of four sections measuring attendance, involvement, importance, and facilitators/barriers: https://ju.se/en/research/research-groups/child/projects/picture-my-participation.html
We used the first two sections in this study. The interviews were conducted by a social worker living in the area and familiar with the culture and language.
The dataset consists of three (3) files:
• Data_set_PMP-I_Andrews_et_al.xlsx
• Variable_list_PMP-I_Andrews_et_al.pdf
• Picture_My_Participation_2019.pdf (the survey used)

Målet med denna studie är att jämföra deltagande inom domänerna närvaro och medverkan för barn och unga med cerebral pares (CP) i ett låginkomstområde i östra Uganda. Åttiotvå barn och unga med CP och 81 barn och unga utan CP deltog i studien (alla 6-22 år gamla). Information om deltagande i närvaro och medverkan samlades in för 20 aktiviteter genom instrumentet "Picture my participation".

Åttiotvå barn och ungdomar mellan 6-22 år med cerebral pares och 81 ålders- och köns-matchade barn och ungdomar utan cerebral pares deltog i studien. Motorisk funktion, egenvård och sociala funktioner undersöktes och målsmän intervjuades på deras barns vägnar med Picture My Participation (PMP). PMP mäter delaktighet i 20 aktiviteter i hemmet och samhället, och har utvecklats för att användas i låg- och medelinkomstländer. Instrumentet består av fyra sektioner som mäter deltagande, medverkan, betydelse och facilitatorer/barriärer: https://ju.se/en/research/research-groups/child/projects/picture-my-participation.html
I denna studie så använde vi de två första sektionerna. Intervjuerna utfördes av en socialarbetare som bodde i studieområdet och är familjär med kulturen och språket.

Datasetet består av tre (3) filer:
• Data_set_PMP-I_Andrews_et_al.xlsx
• Variable_list_PMP-I_Andrews_et_al.pdf
• Picture_My_Participation_2019.pdf (enkäten som använts)
Delaktighet för barn och unga med cerebral pares i Uganda: aktivitetsnärvaro och medverkan jämfört med jämnåriga utan cerebral pares
Keywords: children; barn; youth; ungdom; Cerebral Palsy; Cerebral pares; Uganda; Uganda; Disabled Children; Barn med funktionsvariation; Low-income country; Låginkomstland; participation; delaktighet; Medical and Health Sciences; Medicin och hälsovetenskap; Neurology; Neurologi; Pediatrics; Pediatrik; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin